Respons Bawang Putih pada Berbagai Frekuensi Penyemprotan Pupuk Cair Organik Mikro - Baiq Nurul Hidayah; Muhammad Tahir Hamsyah; Mohammad Rani; Nurhaedah Nurhaedah; Sirajuddin Sirajuddin; Imam Gazali; Supardi Supardi; Agus Hafid; Ai Rosah Aisah; Nani Herawati (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2024)
Garlic is a horticultural commodity with high economic value in Indonesia. For optimal growth and yield, garlic plants need macro and micronutrients from fertilization. Micronutrients can be fulfilled, such as by spraying micro-organic liquid fertilizer. This research aims to determine the effect of various spraying frequencies of Micro Organic Liquid Fertilizer – Micro Magic (PCOM-MM) on the growth of garlic plants. The garlic variety planted was local Sangga Sembalun using a 1-factor Randomized Block Design with 4 treatments of spraying frequencies: 1) without spraying PCOM-MM, 2) spraying PCOM-MM one time every two weeks, 3) spraying PCOM-MM one time a week, and 4) spraying PCOM-MM two times a week. Each treatment was repeated three times: Garlic Response to Micro Liquid Organic Fertilizer therefore, there were twelve treatment plots. The results of various PCOM-MM spraying frequencies did not significantly differ in plant height, root length, and bulb diameter. Still, they significantly differed in the number of leaves and leaf width. Further research on the PCOM-MM spraying with various spray concentrations higher than those stated on the product packaging, numerous garlic varieties, and different types of land is needed.